2018
DOI: 10.1107/s2056989018010034
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal X-ray diffraction study of a host–guest system comprising monofunctionalized-hydroxy pillar[5]arene and 1-octanamine

Abstract: The crystal structure and supra­molecular inter­actions between a hy­droxy-functionalized pillarene and 1-octa­namine guest mol­ecule, which forms an inter­esting host–guest system, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this product, the signals for the –CH 2 – groups of the butyl chain in 1 H NMR appeared in the upfield region for the n -butylamine itself indicating the penetration of the butyl chain into the cavity of the pillar either inter- or intramolecularly. Importantly, the penetration of the alkyl chain of n -alkylamine into the pillar cavity due to the amine–phenol interaction is supported by Al-Azemi et al through the crystal structure analysis . To further support the mechanism, as shown in Figure c, a time-dependent 1 H NMR spectrum of 1 was followed in the presence of n -butylamine and triethylamine in CDCl 3 (Figure S16).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In this product, the signals for the –CH 2 – groups of the butyl chain in 1 H NMR appeared in the upfield region for the n -butylamine itself indicating the penetration of the butyl chain into the cavity of the pillar either inter- or intramolecularly. Importantly, the penetration of the alkyl chain of n -alkylamine into the pillar cavity due to the amine–phenol interaction is supported by Al-Azemi et al through the crystal structure analysis . To further support the mechanism, as shown in Figure c, a time-dependent 1 H NMR spectrum of 1 was followed in the presence of n -butylamine and triethylamine in CDCl 3 (Figure S16).…”
Section: Resultsmentioning
confidence: 67%
“…Importantly, the penetration of the alkyl chain of n-alkylamine into the pillar cavity due to the amine−phenol interaction is supported by Al-Azemi et al through the crystal structure analysis. 60 To further support the mechanism, as shown in Figure 8c, a timedependent 1 H NMR spectrum of 1 was followed in the presence of n-butylamine and triethylamine in CDCl 3 (Figure To realize the sensitivity of 1 toward amine detection, it was observed that the peak at 547 nm in the UV−vis spectrum and color of the solution of 1 emerged from the presence of either 1 equiv or below 1 equiv amounts of primary, secondary, and tertiary amines. Among the amines, tertiary amines responded quickly below 1 equiv amount.…”
Section: Density Functional Theory Studymentioning
confidence: 99%
“…Up to now, two different strategies have been employed in the construction of such organic-inorganic hybrid composites/ systems by using either supramolecular interactions or covalent bonds. 49 The larger-sized pillar[n]arene cavity (n ≥ 10) 50 could directly include fullerene in a stoichiometry of 1/1 to form the host-guest inclusion, [51][52][53][54][55][56][57] where the cavity of pillararene was fully occupied without any other possible applications. Interestingly, the proper functionalization of smallersized pillar[n]arene (n = 5) by e.g., alkyl groups could also flexibly enlarge the hydrophobic and electron-rich pillararene cavity, making it possible to capture "fixed-sized" fullerene.…”
Section: Bing LImentioning
confidence: 99%